Perencanaan Koordinasi Isolasi Peralatan Tegangan Tinggi Gardu Induk 150 kV Berdasarkan Arus Surja Petir Pada Sistem Interkoneksi Sumatera Bagian Selatan (Sumbagsel) dan Sumatera Bagian Tengah (Sumbateng) - Yusreni Warmi; Dasman Dasman; Minarni Minarni (Jurnal Momentum ISSN 1693-752X)
The simulation results show the influence arrester laying, the magnitude of overvoltage that occursin power transformer such as placement system arresters on transmission 150 kV transformer greatly affect the amount of voltage surges that occur in transformers and arresters, surge and affects the amount of current flowing in the wire melting of CO. System-1 is an effective placement system arresters. In terms of voltage surges generated: the system is not easy to produce high voltage surges that of the four systems, the system-1 is a system that produces the low-voltage surge in both the transformer and the arresters. Overvoltage that occurs in the equipment due to lightning surge currents greater value if the distance laying lightning arresters of the equipment is the greater, for the laying of the lightning arrester at a distance of 6 meters, the peak voltage value on each piece of equipment, CT is 543.837 kV, CB is 566.659 kV, DS is 579.357 kV Arrester is 527.884 and 527.884 kV transformer is Power. Meanwhile, at a distance of 10 meters, overvoltage arising on each piece of equipment increases, the CT is 543.600 kV, CB is 567.269, DS is 579.381, 528.097 kV Arrester is and is 528.123 kV Power Transformer. The more steep lightning current waveforms into the substation, the greater the value of the voltage over to the protected equipment. For laying the same distance is 6 meters, acquired 527.884 kV to 87 kA lightning, 8/20, 559.222 kV to 87 kA lightning, 1/70, 558.803 kV to 87 kA lightning strike, 1.2 / 50.